PRIVATE EDUCATION AS A WAY TO ENHANCE COMPETITIVENESS OF THE EDUCATION SECTOR OF UKRAINE - Danilovich-Kropyvnytska , M.; Khmelyuk , V (Theory and Practice of Public Administration, 2021)
The work examines theoretical aspects of the integration between private and public education in Ukraine, ways to reform and promote competition among private higher education institutions.Radical changes are ripe in the system of higher education in Ukraine, which are reflected in the rapid implementation of mechanisms for restructuring training, public management decisions and integration of educational processes. Under these conditions, private educational institutions can respond quickly to market conditions and implement the necessary training programs that will be an instant response to market needs and provide additional competitive advantages for potential student consumers. However, the country has not created the conditions necessary for the development of the private education segment and ensure its competitiveness for the modern labor market.Previous research by Ukrainian scientists has not paid enough attention to the segment of private educational services, where there is significant potential, scientific and technical base, there are prominent Ukrainian scientists and professional teachers. Therefore, the purpose of this article is to determine the factors of competitive advantage of private higher education institutions and the conditions for their improvement.The most popular fields of knowledge now are the public administration sector, information and communication technologies, banking and insurance, marketing, advertising, international relations, linguistics, tourism, logistics, management. All these specialties can be mastered in public, municipal and private institutions of higher education. Domestic private higher education institutions are divided into purely private and corporate. Each of them has its own management structure, dynamics of development, legal form, differs in areas and form of ownership, the level of accreditation. Private educational institutions independently decide on the accreditation of the educational program, which is responsible for the direction of obtaining the appropriate qualification and choose different forms of education: full-time, part-time, distance, blended or other. The expansion of the network of private educational institutions should overcome the distrust of entrants and their parents, because they are more flexible, innovative, have the opportunity to invite representatives of the best international universities and business experts to teach. The competitiveness of the university directly depends on the professionalism of the teaching staff, their professional experience and integration into the modern business environment.Taken four private educational institutions, the study conducts a comparative analysis of critical factors that affect their competitiveness. It defines a certain vision of how to develop educational services as an area of potential entrepreneurial activities.